Óleo de resíduo polimérico do tipo polipropileno como combustível alternativo para motores do ciclo diesel - Cavalheiro, Orlando de Lima (2018)
This work presents a characterization methodology of the oil produced from the pyrolysis of polypropylene (PP) disposed as Municipal Solid Waste (MSW), aiming its use as alternative fuel for diesel cycle engine. Samples of virgin PP and waste PP were characterized by thermal degradation by Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) to obtain a comparison between the samples and to determine an appropriate range of parameters for pyrolysis tests, such as pyrolysis temperature, pyrolysis reaction time, heating rate and nitrogen rate flow. Samples of waste PP pyrolysis oil, obtained by the pyrolysis tests in a batch reactor, were purified through an adsorption process with activated carbon assisted by vacuum filtration, aiming to reduce the particle matter and the intense coloration of this oil. The purified waste PP pyrolysis oil characterization was divided into two parts: one with Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography coupled with Mass Spectrometry (GC-MS) in which a comparison between this oil and the commercial S10 diesel fuel was performed, and another that involved the analysis of density, viscosity, pH and heating value. The characterization results obtained to purified waste PP pyrolysis oil were quite similar to the ones obtained to commercial S10 diesel fuel, showing that this oil has characteristics of fuel oil. It can also make possible to remove part of PP polymer, classified as MSW, from environmental disposal.